A qualitative descriptive exploration of the educational and career plans of early career neonatal nurses and midwives: An Irish perspective. (January 2018) - Coughlan, Linda Martina; Patton, Declan
Abstract: The scarcity of appropriately qualified nurses and midwives is a major obstacle in achieving an effective health system. Neonatal nurses and midwives require a high level of skill and education to fulfil their role. It is also an area that sees high staff turnover rates. For this study a descriptive qualitative approach was used to ascertain early career neonatal nurses' and midwives' experiences of further education, their future career plans, and their perceived facilitators and barriers to further education and career progression. After receiving ethical approval, twelve nurses and midwives were recruited across three tertiary level neonatal units in Ireland. Semi structured interviews were carried out and interview transcripts were subsequently analysed using Attride-Stirling's (2001) Thematic Networks to deduce themes from the data. Support and involvement, mentoring, and career progression and retention were the three main themes identified upon analysis of the data. The majority of participants identified definitive career plans but some felt their goals were unachievable in their current workplace. Consequently a large number of participants have plans to leave their employment in neonates and pursue a career in other areas of nursing. Staff appraisals and succession planning programmes may assist early career nurses and midwives in focusing on their individual career goals, leading to a greater uptake of further specialised education and improved retention of neonatal nurses and midwives.